Biosimilars for psoriasis: clinical studies to determine similarity. (28th May 2017) - Blauvelt, A.; Puig, L.; Chimenti, S.; Vender, R.; Rajagopalan, M.; Romiti, R.; Skov, L.; Zachariae, C.; Young, H.; Prens, E.; Cohen, A.; van der Walt, J.; et al.
Summary: Biosimilars are drugs that are similar, but not identical, to originator biologics. Preclinical analytical studies are required to show similarity on a molecular and structural level, but efficacy and safety studies in humans are essential to determining biosimilarity. In this review, written by members of the International Psoriasis Council, we discuss how biosimilars are evaluated in a clinical setting, with emphasis on extrapolation of indication, interchangeability and optimal clinical trial design. Abstract : What's already known about this topic? Clinical studies, in addition to preclinical data, are required for regulatory approval of biosimilars. Biosimilar clinical trials are designed with smaller sample sizes than those required for approval of new biological agents, and are not required for every indication of the originator. What does this study add? The International Psoriasis Council provides suggestions for biosimilar clinical trial design and describes psoriasis as the best disease model for tumour necrosis factor‐blocker biosimilar studies.